Developing a White-Box Public Key Cryptography and Its Application for Building a Secure Data Storage - Nikita Evgenyevich Arykov; Sergey Fedorovich Krendelev (Безопасность информационных технологий, 2014)
In the article existing cryptographic solutions of protecting confidential data were analyzed and the basic problem of a small number of secret parameters was formulated. This paper describes an algorithm that depends on a large number of secret parameters, based on one-to-one functions and two applications that allow to encrypt user passwords.